Coefficient estimates for starlike and convex functions related to sigmoid functions - Raza, M.; Thomas, D. K.; Riaz, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5 We give sharp coefficient bounds for starlike and convex functions related to modified sigmoid functions. We also provide some sharp coefficients bounds for the inverse functions and sharp bounds for the initial logarithmic coefficients and some coefficient differences.